Optimising nutrient potential from compost and irrigation with wastewater to meet crop nutritional requirements - Chipula, Grivin (Cranfield University, 2013)
Globally agricultural production is facing serious challenges to provide adequate food supply to meet a growing population. However, the reduced capacity of soil to support and sustain agricultural production as a result of soil fertility decline is impacting negatively on agricultural growth. Increase in the price of inorganic fertilisers and limited availability of nutrients from organic amendments has reduced progress in improving soil fertility. This research therefore aims at contributing knowledge towards evaluating the maximisation/optimisation of nutrients in compost and secondary treated sewage effluent (STSE) amended soils to meet the nutritional requirements of crops for sustainable crop production and environmental protection. STSE was irrigated on soils (sandy loam and clay loam) amended with greenwaste compost in soil incubation, glasshouse/pot and lysimeter studies. Perennial ryegrass (Lolium perenne) was grown in the pots and lysimeter studies. The incubation experiment showed that for a clay loam, N mineralisation in treatments with STSE alone and combinations of compost and STSE was higher than the applied N. Increasing compost quantity in compost and STSE nutrient integration resulted in reduced net N mineralisation in the clay loam soil. In the sandy loam, increasing compost contribution in compost and STSE nutrient integration resulted in an increase in net N mineralisation. Cation exchange capacity, microbial diversity, quality of available carbon and drying and rewetting cycles influenced the net nitrogen mineralisation dynamics in both soil types. Increasing the contribution of STSE while reducing compost quantity resulted in increased nitrogen use efficiency and ryegrass dry matter yield. The environmental threat to ground and surface water pollution through NO3 --N leaching may be enhanced by the inclusion of STSE in integrated compost and STSE nutrient supply to plants. Similarly, the threat to eutrophication due to phosphorous leaching is likely to be higher with integration of compost and STSE. Ryegrass dry matter yield reduced with increasing compost contribution while the concentration of N in ryegrass herbage for the combinations of compost and STSE was above the minimum requirement for N in herbage for productive grazing and dairy cattle in the pot experiment. Using compost and STSE of similar characteristics, the ideal approach to maximise nutrient potential from compost through irrigation with STSE is when 25% compost is integrated with 75% STSE with respect to nitrogen supply.
Keywords: Nutrient integration; irrigation; compost; effluent; nitrogen mineralisation